Breastfeeding and Adult Personality. Issue 5 (September 2016) - Sutin, Angelina R.; Stephan, Yannick; Terracciano, Antonio
Abstract: Five‐Factor Model personality traits are implicated in long‐term health‐risk behaviours and outcomes. Less research has addressed how early life experiences are associated with individual differences in these traits in adulthood. We examine whether having been breastfed is associated with adult personality and well‐being in the National Longitudinal Study of Adolescent to Adult Health. At Wave 1, caregivers reported whether the target child had been breastfed. At Wave 4, participants ( N   = 13, 113; 53% female; M age  = 28.98) completed measures of psychological functioning. We tested for mean‐level differences in the traits by breastfeeding status (yes/no) and by the duration of breastfeeding, controlling for basic demographic factors and early life factors that could confound the breastfeeding–personality association (e.g. mother education). Participants who had been breastfed scored lower in neuroticism, anxiety, and hostility and higher in openness and optimism than those not breastfed. A curvilinear relation suggested that neuroticism was lowest for those breastfed for 9–12 months and highest for those either breastfed for >24 months or exclusively bottle‐fed. Breastfeeding was unrelated to conscientiousness or state psychological functioning. This research suggests long‐term psychological benefits to breastfeeding and indicates that early life experiences are associated with traits that are consequential for adult health. Copyright © 2015 European Association of Personality Psychology